2005
DOI: 10.1080/02699050400004294
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subtle cognitive-communication deficits following acquired brain injury: A normative study of the Functional Assessment of Verbal Reasoning and Executive Strategies (FAVRES)

Abstract: The FAVRES provides a reliable, functional and quantifiable measure of the cognitive-communication difficulties of individuals with ABI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…The FAVRES is sensitive to impairments in high-functioning individuals (MacDonald, 1998). The adult version of the FAVRES has been shown to discriminate well those with TBI from typically developing individuals (MacDonald and Johnson, 2005) and also has been validated in relation to return to work (Isaki and Turkstra, 2000;MacDonald and Johnson, 2005). Administration time is * 60 min.…”
Section: Executive Functioningmentioning
confidence: 99%
“…The FAVRES is sensitive to impairments in high-functioning individuals (MacDonald, 1998). The adult version of the FAVRES has been shown to discriminate well those with TBI from typically developing individuals (MacDonald and Johnson, 2005) and also has been validated in relation to return to work (Isaki and Turkstra, 2000;MacDonald and Johnson, 2005). Administration time is * 60 min.…”
Section: Executive Functioningmentioning
confidence: 99%
“…The latter results indicate the test can discriminate between performances of those with and without ABI although not perfectly. The authors concluded the test is a reliable quantitative measure of cognitive‐communication performance 20 …”
Section: Resultsmentioning
confidence: 98%
“…Not surprisingly, this has produced something of an overabundance of potential terms. These include 'cognitive-language' (Hagen, 1982), 'cognitive-pragmatic' (McDonald, 1992a), 'high-level' (and indeed 'higher-level') language (Cook et al, 2004;Hinchliffe et al, 1998a;Laakso et al, 2000;Lethlean & Murdoch, 1997;Moran & Gillon, 2004), 'higher order' language (Hinchliffe et al, 1998a), 'complex' and 'more complex' language (Hinchliffe et al, 1998a;Wapner et al, 1981), 'pragmatic' (Channon & Watts, 2003;Martin & McDonald, 2003;Meilijson et al, 2004), 'cognitive-communicative' (and 'cognitive-communication';Chapman et al, 2004;MacDonald & Johnson, 2005;Sbordone, 1988;Turkstra et al, 2005) and 'cognitive-linguistic' (cognitive-language; Cherney, 1991;Ellmo et al, 1995;Hinchliffe et al, 1998b;Whelan & Murdoch, 2005).…”
Section: Terminologymentioning
confidence: 98%